The relationship between teachers’ zest for work and teaching motivation: the mediating role of achievement goals - Aytaç, Alper; Şahin, Çiğdem; Görgülü, Deniz; Dilber, Yaşar; Direk, Ayhan (Frontiers in Psychology, 2024)
Objective: This study aims to investigate the mediating role of achievement goals in the relationship between teachers' zest for work and teaching motivation.The research was designed using the relational survey model. The research sample consisted of 518 teachers working in various cities in Turkey in 2023-2024 academic year fall semester. A convenience sampling method was used in sampling. Three Likert-type scales were used as data collection tools. In the data analysis, firstly, the data suitability to normal distributions was examined. As a result of the analysis, kurtosis and skewness values were examined and it was assumed that the data were normally distributed. SPSS Process extension was used to analyze the data.According to the research results, teachers' zest for work positively and significantly predicted strong and positive achievement goals. In addition, teachers' achievement goals significantly and positively predicted their teaching motivation. Additionally, teachers' zest for work positively and significantly predicted their teaching motivation. Moreover, it can be inferred that achievement goals for students have a mediating role in the relationship between teachers' zest for work and teaching motivation. In this context, it is suggested that policies that increase teachers' teaching motivation should be prioritized.